Beta human papillomavirus E6: a menace to genomic integrity - Dacus, Dalton (Kansas State University, 2022)
Beta genus human papillomaviruses ([Beta]-HPV) are associated with the development of cutaneous squamous cell carcinomas (cSCC) by destabilizing the genome. In vitro and in vivo studies indicate the [Beta]-HPV E6 and E7 proteins act as co-factors with ultraviolet radiation (UV) to cause genome destabilization. However, the E6 protein from [Beta]-HPV type 8 (8 E6) induces tumor formation in mice without UV exposure, but the mechanisms driving carcinogenesis are unclear. In this dissertation, we investigated UV-independent mechanisms of HPV8 E6-induced genome destabilization. In silico screens validated by cell line characterization showed that 8 E6 deregulated the Hippo pathway by destabilizing the histone acetyltransferase, p300. Hippo pathway disruption increased cell proliferation and attenuated cell death in response to failed cytokinesis. While 8 E6 alone was unable to promote long-term proliferation after cytokinesis failure, we demonstrated that 8 E6 combined with TERT expression rescued long-term proliferation. However, this resulted in increased genomic instability in the form of ploidy changes. Furthermore, we showed 8 E6 decreased the abundance of anaphase bridge resolving helicase, Bloom syndrome protein (BLM). The diminished BLM was associated with increased segregation errors and micronuclei. 8 E6 reduced antiproliferative responses to micronuclei and time-lapse imaging revealed 8 E6 promoted cells with micronuclei to complete mitosis. Finally, whole-genome sequencing demonstrated that 8 E6 induced a mutational phenomenon known as chromothripsis, in 9 chromosomes. Overall, the findings from my dissertation provide insight into the processes by which 8 E6 induces genome instability in the absence of UV exposure.
Keywords: Human papillomavirus; Cancer; Chromothripsis; p300; HPV8